Community Capacity Building for Tourism Development in the Local Communities of Shiraz, Iran - Aref, Fariborz (2009)
The main purpose of the study is to assess building community capacity for tourism development. A lack of community capacity has been identified as a barrier to tourism development in third world countries. Hence, the study provides a focused academic analysis of this issue within tourism development in Shiraz. The data for this study was collected from community leaders and local residents. Eight operational dimensions in three levels of (individual, organizational and community) were used to measure the level of community capacity building for tourism development. Information for this study was derived from questionnaires and focus group discussions. Descriptive statistics, correlations, t-test, one-way Anova, and multiple regression analysis were also performed on the complete data set. Descriptive Statistics were used to determine the level of community capacity building as well as its barriers for tourism development. The findings show that, generally, community capacity building in the study area is low. However, the community capacity building in the old district is higher than the new district of Shiraz. The findings also show sense of community and individual level are the highest in comparison with other dimensions and levels. These finding also have been supported by focus group discussion. T-test results also confirmed higher level of community capacity building for the old district. One-way anova result also showed that the level of community capacity building in cultural activities is higher than other types of tourism activities. The study also has identified that lack of community capacity building is an important barrier for tourism development, especially in the new district. In support of this finding, the focus group has also confirmed the barriers of community capacity building. This study also investigated community perceptions towards tourism impacts and its relationship with level of community capacity building. The study proved that there are broadly similar views among the leaders and local residents’ perceptions toward tourism impacts on local communities. The correlation result showed that there is a significant relation between economic impacts and the level of community capacity building for tourism development. The correlations result also confirmed that there were significant relationships between the level of community capacity building and the leaders’ age, length of residence, length of position, income, tourism income, tourism job and family engaged in tourism activities. Lastly, multiple regression analysis indicated that approximately 74 percent (R² =.737) of the variance in community capacity building was predicted by the leaders’ income, tourism income, extra activities, length of residence, educational level, and family engaged in tourism industry. According to the result, the largest beta coefficient is the leaders’ income. It is expected that the findings of this study could be utilized by the community leaders and tourism developers for future follow-up studies and reassessment of community capacity building for tourism development in their communities.